Implementasi Socket Programming dalam Penyesuaian Ukuran Paket pada Jaringan IPv6 - Kesit Budi Kusumo; Primantara Hari Trisnawan; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
In IPv6 (Internet Protocol Version 6), fragmentation is only allowed on the end host side. As a result, IPv6 packets can experience potential failures in delivery. The potential failure is caused by two things. First, the packet size exceeds the MTU (Maximum Transmission Unit) value. Second, the router is configured by the network administrator to filter ICMPv6 Packet Too Big packets. Existing solutions are PMTUD (Path Maximum Transmission Unit Discovery), PLPMTUD (Packetization Layer Path Maximum Transmission Unit Discovery), and MSS (Maximum Segment Size) Clamping. However, these three solutions cannot be used in UDP (User Datagram Protocol) based communication and not all operating systems activate these features. Therefore, this research presents a solution by implementing socket programming through the case of audio streaming. With socket programming, research results show communication can take place well. This has been tested through several scenarios. In the first scenario, the results of the experiment without ICMPv6 Packet Too Big filtration and uniform MTU values are smooth communication with a small average packet loss below one percent. In the second scenario, the test results accompanied by ICMPv6 Packet Too Big filtration and MTU values are not uniformed are the same as in scenario one. The difference is that there is a pause as a result of the congestion control mechanism by the DCCP (Datagram Congestion Control Protocol) streaming protocol and limitation on socket buffer.